Development of an Eight-channel Full-bridge Strain Signal Synchronous Collector. Issue 1 (1st February 2023) - Tao, Aihua; Xu, Yue; Liu, Wang; Zhou, Zhijian; Lyu, Qing; Qiao, Liyan
Abstract: Wind tunnel test is widely used in automotive, aerospace, and other fields. The overall effect of the test depends on the accuracy of the data collected by the acquisition system. To collect the balanced strain signal with high precision, an eight-channel full-bridge strain signal synchronization collector is developed in this paper. The article gives the hardware and software design of the collector, respectively. The hardware adopts a modular design with STM32H743 MCU and MAX10 series FPGA, which implements the signal condition, the Butterworth low pass filter, the analog to digital conversion, and the wireless data transmission with WIFI. In terms of software design, the article not only gives the firmware of MCU and FPGA but also designs the software of the host computer with LabVIEW. Finally, the data are tested and analyzed according to the requirements of technical indexes.